Prevention rather than therapy - Maurer, Martin H. (Deutsches Ärzteblatt, 2012)
The authors report epidemiological data for medical histories of maltreatment, abuse, or neglect of children (4). These data make an important contribution towards child protection for the better assessment of risk factors. At the same time, I want...